Transformation to a renewable electricity system in Austria: Insights from an integrated model analysis - Claudia Kettner; Michael Böheim; Mark Sommer; Robert Gaugl; Udo Bachhiesl; Lia Gruber; Thomas Florian Klatzer; Sonja Wogrin; Kurt Kratena (Austrian Institute of Economic Research (WIFO), 2023)
We analyse the (techno- and macro-)economic and distributive effects of a transformation to a renewable electricity system in Austria by 2030, as stipulated by the Austrian government. For the analysis, the macroeconomic model DYNK and ATLANTIS, a partial model of the electricity market, were expanded and linked. Four transformation scenarios conforming with the 100 percent renewable electricity target in Austria on a national balance are examined, integrated into a consistent scenario for the development of the European electricity system. Additionally, sensitivity analyses with respect to the gas price are performed. Although all scenarios achieve 100 percent RES-E on a national balance, the analysis shows that electricity from gas-fired power plants will still be needed in 2030 to balance variable renewable generation, to avoid grid congestion, and for heat generation from combined heat and power plants in winter months. Another main conclusion from the simulations is that the transition towards a renewable electricity sector is almost neutral from a socio-economic perspective. It does neither reveal harmful impacts nor lead to high multiplier effects from additional investment. With high natural gas prices in the sensitivity scenarios a decrease in GDP and household income, which might motivate redistributive policies, can be observed.
Keywords: 330; renewable electricity; Austria; model linkage; macroeconomic model; electricity system model